2000
DOI: 10.1006/viro.2000.0622
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genomic Sequence of a BLV Strain from a Holstein Cow from Argentina

Abstract: DNA was extracted from the peripheral blood of a seropositive, PCR-positive, BLV-infected Holstein cow (No. 38) from Argentina. The DNA was amplified via PCR with a series of overlapping primers encompassing the entire BLV proviral DNA. The amplified BLV ARG 38 DNA was cloned, sequenced, and compared phylogenetically to three other full-length BLV sequences. Characterization of its deduced proteins and its relationship to other members of the PTLV/BLV genus of retroviruses are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 8 publications
3
38
0
1
Order By: Relevance
“…A consensus sequence was obtained with the remaining sequences to recalculate the substitution numbers, and 31 nucleotide substitutions were observed, with an average of 7.7 per sequence (1.4 %), most of them silent (74.2 %) and transitions (83.8 %). These results are similar to these obtained in previous reports (Coulston et al 1990, Dube et al 1997, Dube et al 2000, Camargos et al 2002. The sequences D00647 and K02120 were excluded from aminoacid alignment (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A consensus sequence was obtained with the remaining sequences to recalculate the substitution numbers, and 31 nucleotide substitutions were observed, with an average of 7.7 per sequence (1.4 %), most of them silent (74.2 %) and transitions (83.8 %). These results are similar to these obtained in previous reports (Coulston et al 1990, Dube et al 1997, Dube et al 2000, Camargos et al 2002. The sequences D00647 and K02120 were excluded from aminoacid alignment (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In all sequences deletions and insertions were observed. Insertions and deletions were not observed in BLV pol and env sequences (Coulston et al 1990, Dube et al 1997, Dube et al 2000, Camargos et al 2002, Monti et al 2005. The sequences D00647 and K02120 probably had sequencing errors, as mentioned by others (Dube et al 2000).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Some of the mutations were detected in one isolate only while some of them were found in other isolates. Out of 18 mutations, found in this study, only four namely A20G, C399T, T400C and T449C, have been already described (6,7,17). Six mutations were located in regulatory elements: at glucocorticoid responsive element (T147C), interferon regulatory factor-binding site (T465C, C473T), and three substitutions T-> C, C -> T (T393C, C399T, T400C) were found in downstream activator sequence.…”
Section: Resultsmentioning
confidence: 68%
“…Strains D0067 and K02120 were positioned in different groups, but were clustered closer. Notably, Brazilian strain 23M clustered in a separate group from others of the same location, but together with strains from Argentina, ARG41 and AF257515, which are characterized by low and high replication rates, respectively (Dube et al, 2000). Moratorio et al (2010) identified a higher degree of genetic variability, with 7 different BLV genotypes circulating in the South American region and 2 genotypes of BLV in Brazilian herds using the env gene for phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 98%